2004
DOI: 10.1039/b409254f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds in “push-pull” enamines

Abstract: A comparison of hydrogen bond strengths in various enamines was made by monitoring the differential shifts Dd(X) as the difference of NMR chemical shifts between E and Z forms of the nuclei directly involved in hydrogen bonding, i.e., X = 15 N, 1 H, 17 O atoms. The interpretation of these differential values was aided by ab initio calculations and X-ray derived geometric parameters for selected compounds. It is shown that Dd(N 1 H) and Dd( 15 N) give conclusive results and their changes are rationally interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…We believe that this is a manifestation of the aforementioned buttressing effect of the S=O group on the C-3-H-3ax and C-5-H-5ax bonds and, circuitously, on the Si-C bonds. The buttressing effect, by analogy with that of the sulfinyl and sulfonyl groups in enamines [25] should result in shielding of the C-3 and C-5 carbons, i.e., in the γ -effect, and this is what is observed in the spectra (table 1). …”
Section: Methodsmentioning
confidence: 73%
“…We believe that this is a manifestation of the aforementioned buttressing effect of the S=O group on the C-3-H-3ax and C-5-H-5ax bonds and, circuitously, on the Si-C bonds. The buttressing effect, by analogy with that of the sulfinyl and sulfonyl groups in enamines [25] should result in shielding of the C-3 and C-5 carbons, i.e., in the γ -effect, and this is what is observed in the spectra (table 1). …”
Section: Methodsmentioning
confidence: 73%
“…To broaden the range of methods used in systematic studies, we tested if some of the techniques previously used to study hydrogen bonding can also be applied to examine halogen bonding. One of these techniques is NMR spectroscopy since it allows the detection of small changes in chemical shifts upon hydrogen bond formation [30][31][32]. 19 F NMR spectroscopy is of particular interest since halogen bonding requires a positively charged region on the halogen atom, the so-called r-hole [21], which is easily achieved by perfluorinated side chains on the halogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…The trifluoromethyl derivative 1c was prepared by potassium tert -butoxide-assisted addition of ethyl acetoacetate to trifluoroacetonitrile, generated in situ from 2,2,2-trifluoroacetamide . It may be noted that the enamino keto esters 1a – k are capable of existing as two geometrical isomers . Careful examination of proton NMR spectra of these enamino keto esters revealed that they exist as E -isomers, as the two amino protons showed separate signals approximately at 5.5 and 11 ppm.…”
Section: Results and Disscussionmentioning
confidence: 98%
“…15 It may be noted that the enamino keto esters 1a−k are capable of existing as two geometrical isomers. 16 Careful examination of proton NMR spectra of these enamino keto esters revealed that they exist as E-isomers, as the two amino protons showed separate signals approximately at 5.5 and 11 ppm. In the E-geometry, one of the amino protons forms an intramolecular hydrogen bond (N− H•••O bond) with the acyl oxygen and thus appears downfield at around 11 ppm.…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation